Aesthetics Of Aeng Tong-Tong Village Kris As An Effort To Preserve The Life Of The People Of Sumenep Madura - Maharani, Oktaberia Sakti; Lodra, I Nyoman; Supratno, Haris (LPPM Institut Seni Indonesia Padangpanjang, 2023)
The value of the keris aesthetic in the tong-tong village as a form of cultural beauty for the life of the Sumenep people changes the community paradigm about the aesthetics of keris, keris as a form of symbolic ingenuity, or becomes a collection object that is seen aesthetically. Keris is also a tool for various activities. Finally, the function of the dagger is as an art object. This study used qualitative descriptive research with a purposive sampling approach followed by the collection of observational data, interviews, and documentation. The results showed that the basic materials of the keris are iron, steel, and nickel. At the same time, the aesthetic value that can be classified is determined by how many repetitions of the folding and forging process (saton). The more folding, the softer the prestige pattern will be produced. The forms of keris found in Aeng Tong-tong village are Keris Keraton Sumenep, Keris Dhamar Sumenep, Keris Gati Pamor Brahma Watu Sumenep, Carubuk Luk 7 Sumenep, Keris Senamper Ngulit Watermelon Sumenep, Keris Brojol Sepuh Dalem Sumenep, Keris Empu Koso Pamor Jung Madura Sepuh, each of these dagger forms has high aesthetic value and historical value so that the people of the Sumenep area always maintain artistic value, sublime, and also cultural values that have been attached for generations to the people of aeng tong-tong village in general Keywords: Keris, Aesthetics, Value, Art